Avifaunal Diversity and Composition in Shergarh Fort and Surrounding Areas, Baran, Rajasthan, India - Arun Kumar Jatav, Amit kumar, Smriti Johari (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study aims to evaluate birds' diversity and guild status in the Shergarh Fort area and its surroundings in Atru, Baran district of Rajasthan, from July 2023 to June 2024. Through comprehensive surveys, 144 bird species across 18 orders and 48 families were identified and documented. The survey encompassed various habitats within the fort, including green spaces, marshes, and terrestrial environments, revealing 79 resident species, 35 seasonal species, and several rare species based on habitat status. The bird community in the Shergarh Wildlife Sanctuary consists of 34 (25.69%) omnivores, 50 (34.72%) carnivores, 37 (25.69%) insectivores, 7 (4.86%) granivores, 6 (4.16%) frugivores, and other. The varied plant species in the region substantially contribute to the diversity of bird species. The study identified species that are commonly found, species that visit during specific seasons, and species that are included in the Red Data Book and IUCN. This research underscores the variety of bird species observed and catalogued, providing a foundation for further studies. The findings aim to raise public and governmental awareness about the importance of conserving Shergarh Fort and protecting its avian fauna. This study is a critical step toward enhancing conservation efforts and ensuring the region's long-term protection and welfare of bird species.